Sukoreno Site: Lost Classic Civilization - Ainur Rohimah; Joni Wibowo; Ricky Yulius Kristian (Budapest International Research and Critics University, 2019)
The discovery of Statue and Red Bricks (Bata Abang) located in Sukoreno Village. The Red Brick in Sukoreno site has scattered in settlements and suspected that many Red Bricks has been crushed by residents. Being a cultural heritage of the past, this site needs deep attention and is very important to be studied as an Indonesian nation's self-image. The researcher used the folklore method to uncover the surrounding of the cultural and historical context. In addition, through physiological comparative studies, the shape and characteristics of decapitated statue and red bricks with Majapahit relics in Trowulan, it is found that decapitated statues (Sukoreno statues) have physiological characteristics (shapes and models) that are similar to the Nandiswara or Mahakala statues. The first identification lead the researcher how the connection of the Sukoreno Site with The East Majapahit Kingdom. This effort is expected to be able to support the development of the cultural tourism area in Jember Regency and contribute to the retention of assets of national culture, especially the culture of the people in Jember. This research concludes that The Sukoreno Site as an important area and assume The Sukoreno Site as a palace.